Conversion of Malic Acid in to Lactic Acid in Aloevera by using Lactic Acid Bacteria - Gajula2, Dinesh. J1, Deepak kumar. J3, Avinash Tungala1*, Ajay J.Y2, Pradeep (Journal of Phytology, 2011)
Malic acid is an excellent indicator of gel freshness. This acid is produced naturally in the leaves of aloes and other succulents whose cells contain large, water-filled vacuoles. Under poor handling conditions in the presence of bacteria, malic acid can be broken down to form lactic acid. Gram-negative rod bacteria, which grow in some aloe gels, assimilate malic acid and free glucose and produce other organic acids such as lactate or lactic acid. Lactic acid is one of the major products of carbohydrate break-down by lactic acid bacteria during malolactic fermentation (MLF). Malolactic enzyme demonstrated to be present in most lactic acid bacteria but not in other bacteria, catalyzes the reaction: 1 malate + H+-1lactate+Co2. <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Avinash Tungala et al. Conversion of Malic Acid in to Lactic Acid in Aloevera by using Lactic Acid Bacteria. J Phytol 3/3 (2011) 01-11.